2021
DOI: 10.24259/fs.v5i2.12089
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Social Capital of Riau Women Farmer Groups in Building Collective Action for Tropical Peatland Restoration

Abstract: Collective action is important when the activities and costs of restoration cannot all be internalized by the government or when urgent maintenance is required beyond the scope of the restoration project. Collective action can be influenced by social capital. In this study, we examine components of social capital and the factors that affect them. Using key informant interview, household survey, and participant observation, we also identify the extent to which social capital is related to collective action. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
1
6
0
2
Order By: Relevance
“…With such an approach, it seems as if the improvement of conditions and the improvement of people's living standards is carried out efficiently, but in fact the independence of the community cannot grow in a healthy manner. That is why it is often found that projects financed by the govern-ment are poorly maintained and not used optimally (Jalil, et al, 2021). On the other hand, purely self-help projects that are planned, financed, and implemented by the community are rarely neglected.…”
Section: Source: Abstraction Of Research Resultsmentioning
confidence: 99%
“…With such an approach, it seems as if the improvement of conditions and the improvement of people's living standards is carried out efficiently, but in fact the independence of the community cannot grow in a healthy manner. That is why it is often found that projects financed by the govern-ment are poorly maintained and not used optimally (Jalil, et al, 2021). On the other hand, purely self-help projects that are planned, financed, and implemented by the community are rarely neglected.…”
Section: Source: Abstraction Of Research Resultsmentioning
confidence: 99%
“…Examples from the Global South (in countries like Nepal, India, Seychelles and Indonesia - Hiratsuka et al, 2019;Chauhan et al, 2021;Etongo et al, 2021) and Western countries are found to build a stronger nexus between policy makers and scientists (Narayanan et al, 2009;Tabara et al, 2003;Huber-Stearns et al, 2021) by the integration of spatial data and models of wildfire behaviour in decision making. Relevant is the contribution that the impact of wildfires has on strengthening communities with local institutions such as municipalities and fire fighters as evidenced in Australia (Mc Dougall et al, 2014) and in developing countries like Nepal and Indonesia, where collective actions enforced rules for risk mitigation (Sapkota et al, 2015;Jalil et al, 2021). In Mediterranean countries voluntary initiatives at local levels and a series of structural and relational bonding between communities and institutions are found to statistically explain the community's operational capacity and perception of arson level (Górriz-Mifsud et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Although recent studies are addressing some of these measures (Górriz-Mifsud et al, 2019;McDougall et al, 2014;Jalil et al, 2021), there is not yet consideration in risk analysis of the importance that training, capacity building and social bonding between citizens and institutions may have to reduce vulnerability. Ways to achieve this integration are under investigation in the FirEUrisk project at the time this paper is proposed.…”
Section: Fig 1: Types and Number Of Studies Addressing Impacts To Spe...mentioning
confidence: 99%
“…Social networks and participation are important dimensions of social capital in business partnerships between farmers and palm oil companies [98]. Apart from sharing their knowledge through social networks and building strong relationships with the company [99,100], farmers may also engage in decision making and policy implementation to improve the sustainability of their partnerships.…”
Section: Role Of Social Network and Participationmentioning
confidence: 99%